Psychopathology in psychotic disorders: Congruency between self-reported and observer-rated measures highest for affective symptoms and lowest for negative symptoms - Blazhevska Stoilkovska, Biljana; Bajraktarov, Stojan; Novotni, Ljubisha; Markoska Simoska, Silvana; Milutinovic, Milosh; Miceva Velichkovska, Elizabet; Novotni, Gabriela; Jovanovic, Nikolina (Wiley, 2022)
Considering that both observer ratings and patient self-reports on severity of psychopathological symptoms are being used in research and clinical settings, this paper aims to explore the degree of congruence between these two sources. Eighty-two adult outpatients diagnosed with psychotic disorders rated their symptoms using the Brief Symptom Inventory (BSI). Observers assessed patients’ functioning using the Brief Psychiatry Rating Scale (BPRS). Self-ratings (overall BSI) were strongly correlated to observers’ evaluations (overall BPRS). Anxiety/depression symptoms dimension of the BPRS were significantly associated with all nine symptom dimensions of the BSI, while positive symptoms dimension and unusual and withdrawal behavior in the BPRS showed a significant relationship to seven symptom dimensions as measured with the BSI. Mania/activation in the BPRS was significantly and negatively related only to phobic anxiety in BSI. Eight symptom dimensions of the BSI (interpersonal sensitivity was an exception), as well as unusual and withdrawal behavior and positive symptoms in the BPRS were rated as more severe in unemployed study participants. Self-rated paranoid ideation was higher in less educated participants. No sex or marital status differences were found in the BSI and BPRS dimensions. The obtained pattern of correlations implied that congruence was highest in regards to affective symptomatology, followed by positive symptoms, and lowest for disorganization and withdrawal behavior.
Keywords: self-ratings and observer assessment, congruency, psychopathology, outpatients, psychotic disorders